Knowledge, attitudes, and practices regarding metabolic associated fatty liver disease (MAFLD) in elderly patients - Li, Wei (Scientific reports, 2025)
This study investigates the knowledge, attitudes, and practices (KAP) of elderly patients with metabolic associated fatty liver disease (MAFLD). A cross-sectional study was conducted from August to October 2024, involving 404 patients in the Geriatrics Department of Shanghai Sixth People’s Hospital. Participants provided demographic information and completed a structured questionnaire to assess KAP scores. A score of ≥ 70% was considered good for knowledge, attitudes, and practices. Structural equation modeling (SEM) was employed to analyze direct and indirect relationships among the KAP dimensions and identify the pathways through which knowledge and attitudes influence practices. The average age of participants was 72.43 ± 7.88 years. Knowledge, attitude, and practice scores were 13.47 ± 5.40, 28.68 ± 5.04, and 28.01 ± 4.61, respectively. SEM findings indicated that knowledge significantly influenced practice (β = 0.39, P < 0.001), and attitudes also notably impacted practice (β = 0.34, P < 0.001), though knowledge’s indirect influence through attitudes was not significant (β = 0.03, P = 0.363). Overall, these findings highlight inadequate KAP among elderly patients with MAFLD, exemplified by 75.2% being unfamiliar of MAFLD’s progression to cirrhosis or cancer, underscoring the need for targeted educational initiatives to improve self-management and health outcomes.